Rationale of Employee Turnover: An Analysis of Banking Sectors in Nepal - Chaudhary, Manoj Kumar (Talaa : Journal of Islamic Finance, 2022)
The main purpose of this study is to elaborate the reasons of employee turnover in the banking sector of Nepal. The study has opted both primary and secondary source of data to achieve the objective of the study. The structured questionnaires were used to collect the data from the sample banks. Meanwhile, different published and unpublished reports of the selected banks were used for the analysis. The collected data are analyzed with the help of MS-excel, SPSS descriptive statistics.  The finding of the study emphasized that employee tends to leave the current job due to the lack of proper environment and facilities provided by the banks. This study concludes that manager in sample banks to some extent lack awareness regarding to which job embeddedness predict employee turnover intentions. Hence, it is recommended to have a proper plan and policies with reference to the effective payment & reward schemes and motivational strategies to minimize the employees’ turnover.